2005
DOI: 10.1556/abiol.56.2005.3-4.22
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic activity of estradiol evaluated by anin vitromicronucleus assay

Abstract: The objective of the present study was to evaluate possible genetic changes in cultured human lymphocytes treated with estradiol, using the cytokinesis block micronucleus assay. Eight experimental concentrations of estradiol were used (range from 10(-10) M to 0.7 x 10(-4) M). The obtained results indicate that estradiol exhibits aneugenic and/or clastogenic effects, expressed as increased frequency of micronucleated lymphocytes at two highest experimental concentrations used in this investigation. In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The mutagenic potential of these compounds can be expressed only after its metabolic activation, mainly by the cytochrome P450,30 which can be accentuated by other substances or chemicals (alcohol, caffeine, cocaine, tobacco, drugs, etc) 20…”
Section: Discussionmentioning
confidence: 99%
“…The mutagenic potential of these compounds can be expressed only after its metabolic activation, mainly by the cytochrome P450,30 which can be accentuated by other substances or chemicals (alcohol, caffeine, cocaine, tobacco, drugs, etc) 20…”
Section: Discussionmentioning
confidence: 99%
“…This bond can be produced with separate DNA chains, between the bases of the same DNA molecule, or between the DNA and RNA, forming MN during cell division. 30 The collateral effects of alkyl agent treatment include toxicity and cancer due to genetic damage. The mutagenic potential of these compounds can be expressed only after its metabolic activation, mainly by the cytochrome P450, 30 which can be accentuated by other substances or chemicals (alcohol, caffeine, cocaine, tobacco, drugs, etc).…”
Section: Discussionmentioning
confidence: 99%
“…30 The collateral effects of alkyl agent treatment include toxicity and cancer due to genetic damage. The mutagenic potential of these compounds can be expressed only after its metabolic activation, mainly by the cytochrome P450, 30 which can be accentuated by other substances or chemicals (alcohol, caffeine, cocaine, tobacco, drugs, etc). 20 Toxicity, mutagenicity, genotoxicity and cancerogenesis of sexual hormones are the result of a combination of genetic and epigenetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies we demonstrated that 17b-oestradiol induces sisterchromatid exchanges (Djeli} and Djeli}, 2002) and micronuclei (Djeli} et al, 2005) in cultured human lymphocytes. These results are in accordance with findings of genotoxic effects of natural (Ahmad et al, 2000) and synthetic oestrogens (Hundal et al, 1997)…”
Section: Introductionmentioning
confidence: 90%